Capsaicinoids, amino acid and fatty acid profiles in different fruit components of the world hottest Naga king chilli (Capsicum chinense Jacq). (1st January 2018) - Ananthan, R.; Subhash, K.; Longvah, T.
Highlights: Efficient extraction method was standardized for capsaicinoid quantification. Capsaicinoids quantified in three fruit maturity stages and ripened red fruit exhibited highest. Capsaicinoid found highest in placenta compare to other fruit components. Capsaicinoid content in 15 dried Naga king chilli land races were quantified. Amino acid and fatty acid composition analysed in fruit components and whole fruit. Abstract: The world hottest Naga king chilli is cultivated and consumed in Northeast India. Capsaicinoids, amino acids and fatty acids were studied in fruit and fruit components of Naga king chilli. Capsaicinoid content was increased in each ripening stage and maximum level was observed at red color fruits. Total protein and fat content of placenta was 19.41 and 20.36% respectively. Capsaicinoids of placenta (7.35 ± 2.241%) was higher followed by seed (3.83 ± 1.358%) and pericarp (2.91 ± 0.667%). Similarly, essential amino acid content was also higher in placenta compared to other components. Amino acid score ranged from 37 to 38 with cystine and methionine as limiting amino acid. Low level of palmitic, stearic and α-linolenic acid and very high level of linoleic acid were found in seeds. Total polyunsaturates of seeds were higher followed by whole fruit. Naga king chilli is unique due to its high capsaicinoid content and it offers potential crop for the future exploitation.